A static rooftop shading system for year-round thermal comfort and energy savings in hot climates - Juana Isabel Méndez; Luis Ibarra; Pedro Ponce; Alan Meier; Arturo Molina (Heliyon, 2024)
In sun-drenched regions, balancing solar exposure for thermal comfort and minimization of cooling energy presents a key challenge. While passive shading mitigates summer heat gain, it also hinders winter solar benefits, a problem that is echoed by active systems such as photovoltaic panels. Existing adaptive solutions, adjusting to seasonal sun angles, offer flexibility, but introduce complexity, maintenance demands, and potentially higher costs. This study introduces a novel static roof shading system that addresses this knowledge gap. It effectively blocks summer sunrays and allows winter insolation without seasonal adjustments or associated mechanisms. This “install and forget” approach promises improved thermal comfort and reduced energy consumption in hot climates. Rigorous energy simulations in nine different Mexican locations, using a 69 m2 household model, reveal significant temperature improvements. The system delivers up to 30.38% (above 5 MWh) equivalent annual reduction in HVAC usage and 71.3% relative increase in thermal comfort during hot periods. This sustainable solution offers valuable information to address indoor thermal challenges in high-temperature regions, contributing to the advancement of sustainable building technologies.